Kognitives Training von Fremdsprachlernstrategien — Begründung eines neuen Forschungsansatzes der Fremdsprachlernpsychologie - Esser, Ulrich (Wydawcnictwo Naukowe UAM, 1990)
On the basis of empirical evidence, a cognitive-psychological approach is introduced which aims at an optimization of foreign language learning and teaching. The possibilities include a systematic training in foreign language learning strategies in order to improve storage, memorization and retrieval of lexical items in L2.